Levels of Heavy Metals (Zn, Pb, Cd and Cu) In Ulva sp. and Enteromorpha sp. macrophytic Green Algae Along Benghazi Coast Line - ELhariri, Khadija S.; Hamouda, Mohamed S.; ELmughrbe, Mariam M.; Alteerah, Munay A. (International Journal of Scientific Research in Biological Sciences, 2020)
Pollution with heavy metals is one of the most severe marine environmental problems in the world. In this study concentrations of heavy metals (Zn, Pb, Cd and Cu) tested in tow marine green algae Ulva sp. and Enteromorpha sp. Collected from four Sites, Elsaberry, Juliana, Eshbellia and Benghazi port (Elmina) along of Benghazi city Coast. The coast extends to about 18 km at the north east of Libya. The algae samples were collected during the winter and summer seasons 2011 and summer 2012. The results obtained shows that the concentration were found to range from 18.66 mg/kg (Pb), 1.93 - 5.5 mg/kg (Cd) and 2.36 - 6.13 mg/kg (Cu). There was a significant difference in heavy metals concentrations found between the sites and also with seasons. The Enteromorpha sp. showed ability to accumulate heavy metals more than Ulva sp. this could be attributed to the large surface area of the Enteromorpha sp. Generally, the summer concentrations of metals were found to be higher than in winter concentrations and this may be due to high temperature levels that affect the uptake of metals and to the availability and presence of nutrient mainly Nitrogen and phosphorous due to the increase in sewage discharge into the sea during summer time.